Word Formation Processes in the Black Hawk Down Movie Script - Winda Ratnanila (Passage, 2014)
The study entitled Word Formation Processes in the Black Hawk Down Movie Script is aimed at revealing the tokens of acronym, compounding and clipping. This study used Bauer’s (1983) theory of word formation processes. The research method used in this study is a qualitative descriptive method. The result shows that the total number of the target words is 75 tokens. There are 19 acronyms (35 tokens), 18 compounding (26 tokens), and 8 clipping (24 tokens). The most frequently used in acronym is RPG (7 tokens), while in compounding is gunship and roadblock (3 tokens), and in clipping is ammo (10 tokens). It can be concluded that the most popular word formation processes in the movie script is acronym.Keywords: Word Formation Processes, Acronym, Compounding, Clipping